Developing a Hybrid Predictive Model for Measuring Customer Lifetime Value (CLV) based on Marketing and Accounting Data and its Role in Improving Management Decisions: An Applied Study in Iraqi Private Banks - Mohammed, Sadoon A.; Rashid, Maysoon Majeed; Obeid, Israa Kadhim; Mohamed, Mohamed J.; Kamil, Haroon H. (NIU Journal of Management Sciences, 2026)
To boost accuracy in the calculation of Customer Longevity Value (CLV) as a marketing asset, this study aimed to develop and apply a hybrid model between behavioral and perceived marketing data and quantitative and financial accounting data. In addition, it sought to forecast the impact of the outcomes of this model on improvement of the effectiveness and quality of strategic and administrative decisions of the Iraqi private banking industry. To achieve these objectives a questionnaire was designed as a primary tool for data collection which was administered to a representative purposive sample of 150 clients and decision-makers of Iraqi private banks. The data was analyzed statistically using the statistical package for the Social Sciences (SPSS) and the structural equation modeling (SEM), in order to test the validity of measurements and hypotheses. The study yielded a number of key findings: Most notably, the study found a statistically significant difference in accuracy between the suggested hybrid predictive model and one-sided models (either accounting-only or marketing-only) in predicting Customer Longevity Value. Additionally, the results demonstrated that the hybrid model's outputs have a significant and positive impact on the effectiveness of banks' strategic decisions, accounting for 55.5% of the changes in these decisions, especially those pertaining to the best use of marketing resources, the creation of smart customer retention policies, and the design of digital banking services. Based on the macropath analysis, the "Customer Long-Term Value (CLV) measurement accuracy" with the highest overall effect size (0.86) is the main mediator between the combination of marketing/accounts information and the impact on decisions. To protect the sustainability of their competitive advantage, the study recommended rationalizing the amount of promotions and focus on positive profit segments and establishing "bank data integration" units, which combine accounting information systems (AIS) and customer relationship management (CRM) systems, to bring about organizational isolation among Iraqi private banks. Keywords: Customer lifetime value - Marketing and accounting data - Managerial and strategic decisions - Iraqi private banks.